PROFIL KEMAMPUAN LITERASI DIGITAL SISWA SEKOLAH DASAR DALAM PENGGUNAAN MEDIA PEMBELAJARAN JARAK JAUH - Lukman hakim muhaimin; Dadan Dasari (STKIP Subang, 2022)
The COVID-19 pandemic has changed the online learning process from offline to online. One of the references for measuring digital literacy levels is to directly observe the learning process that occurs using platforms that support distance learning. The purpose of this study was to analyze the digital literacy skills of elementary school students in the use of distance learning media and analyze the understanding of digital media of elementary school students in the use of distance learning media. The method used is qualitative with a phenomenological design. Data collection techniques using interview techniques, field observations, and documentation. The data validity technique uses source and technique triangulation. At the same time, the data analysis technique uses an inductive step. The results showed that the students of SD N 1 Brajan had a good level of digital literacy; students knew the benefits of digital media used as learning media, such as understanding the help of the media features used for practical benefits. Meanwhile, in applying digital media, students can also use it as a learning medium. This is because students are used to using these media in everyday life. In contrast, some students have difficulty applying digital media because they have the reason that the cellphones they use are still alternating with their parents, so the infrequent use of digital media will affect students' digital literacy skills. Teachers can make efforts to improve students' digital skills by providing learning media that can provide additional learning in the use of learning media that are foreign to students.